Overexpression of Human SOD1 Leads to Discrete Defects in the Cerebellar Architecture in the Mouse - Afshar, Pegah; Ashtari, Niloufar; Jiao, Xiaodan; Rahimi-Balaei, Maryam; Zhang, Xiaosha; Yaganeh, Behzad; Del Bigio, Marc R.; Kong, Jiming; Marzban, Hassan (Frontiers in Neuroanatomy, 2017)
The human superoxide dismutase 1 (SOD1) gene is responsible for neutralizing supercharged oxygen radicals within the cell. Mutation in SOD1 gene causes amyotrophic lateral sclerosis (ALS). Recent studies have shown involvement of the cerebellum in ALS, although the cerebellar contribution in SOD1 transgenic mice remains unclear. Using immunohistopathology, we investigated the Purkinje cell phenotype in the vermis of the SOD1 transgenic mice cerebellum. Calbindin 1 (Calb1) and three well-known zone and stripe markers, zebrin II, HSP25, and PLCβ4 have been used to explore possible alteration in zone and stripe. Here we show that Calb1 expression is significantly reduced in a subset of the Purkinje cells that is almost aligned with the cerebellar zones and stripes pattern. The Purkinje cells of SOD1 transgenic mice display a pattern of Calb1 down-regulation, which seems to proceed to Purkinje cell degeneration as the mice age. The onset of Calb1 down-regulation in Purkinje cells begins from the central zone and continues into the nodular zone, however it has not been observed in the anterior and posterior zones. In a subgroup of SOD1 transgenic mice in which gait unsteadiness was apparent, down-regulation of Calb1 is seen in a subset of PLCβ4+ Purkinje cells in the anterior zone. These observations suggest that the Calb1− subset of Purkinje cells in the anterior zone, which receives somatosensory input, causes unsteady gait. Our data suggest that human SOD1 overexpression leads to Calb1 down-regulation in the zone and strip pattern and raise the question of whether SOD1 overexpression leads to Purkinje cells degeneration.